2013
DOI: 10.1017/s1461145713000710
|View full text |Cite
|
Sign up to set email alerts
|

Effect of mood stabilizers on DNA methylation in human neuroblastoma cells

Abstract: Unraveling the epigenetic status of neuronal cells in the brain is critical to our understanding of the pathophysiology of psychiatric disorders, which may reflect a complex interaction between genetic and environmental factors. Several epigenetic studies of mood disorders have been conducted with postmortem brains. However, proper interpretation of the results is hampered by our scant understanding of the effects of mood stabilizers on the epigenetic status of neuronal cells. We performed both comprehensive a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
48
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(50 citation statements)
references
References 37 publications
2
48
0
Order By: Relevance
“…While such discrepancies between studies may likely reflect the heterogeneity of clinical phenotypes and underlying etiologies [1], there is also evidence for potential pharmacotherapy-related effects. For instance, Asai et al [45] identified a diverse pattern of carbamazepine-induced CpG hypermethylations and hypomethylations. Among these, we found no overlap with our candidate CpGs.…”
Section: Discussionmentioning
confidence: 99%
“…While such discrepancies between studies may likely reflect the heterogeneity of clinical phenotypes and underlying etiologies [1], there is also evidence for potential pharmacotherapy-related effects. For instance, Asai et al [45] identified a diverse pattern of carbamazepine-induced CpG hypermethylations and hypomethylations. Among these, we found no overlap with our candidate CpGs.…”
Section: Discussionmentioning
confidence: 99%
“…Decreased levels of GSH and changes in glutathione peroxidase (GPx) activity were found in patients with BD (Andreazza et al, 2007b;Gawryluk et al, 2011;Gigante et al, 2011b;Fraguas et al, 2012). Lithium has been shown to decrease oxidative damage and increase GSH in cerebral cortex cell culture (Shao et al, 2005(Shao et al, , 2008Cui et al, 2007) as well as regulating methylation (Asai et al, 2013). D' Addario et al (2012) of reported hypomethylation in post-mortem brain tissue in patients with BD who were on lithium treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Several findings have shown that VPA affects DNA methylation in vitro [13]. We tested whether VPA treatment influenced the DNA methylation levels in bipolar patients by comparing group I (Li-mono) and group II (Li + VPA).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, there are in vitro studies suggesting that VPA may lead to altered DNA methylation [23], which may be a consequence of the strong link between histone modifications and DNA methylation [7]. In neuroblastoma cell lines, VPA had the potential to lead to both hypermethylation and hypomethylation at specific gene sites, with a tendency to an overall shift towards hypermethylation [13]. Similarly, VPA increased global DNA methylation in neuroblastoma cell lines.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation